2005
DOI: 10.1002/bit.20659
|View full text |Cite
|
Sign up to set email alerts
|

An epoch‐making application of discharge plasma phenomenon to gene‐transfer

Abstract: We discovered an epoch-making gene transfer method utilizing discharge plasma. Although an electroporation method is commonly used in present gene transfer experiments, it cannot transfer genes into primary cells sufficiently. The atmospheric pressure discharge plasma employed in this study was originally used for surface treatment of non-biological materials. We hypothesized that it could provide a suitable effect on the surface of target cells and applied it to gene transfer into various types of cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Such a technique would be expected to play an important role in advanced medical technologies like gene therapy and regenerative medicine through establishment of iPS (induced pluripotent stem) cells. A technique that uses discharge plasma irradiation was invented by Satoh, who is one of the authors, and his group in 2002 [4] and was reported by Ogawa in 2005 [5]. Since this technique is free from adverse effect associated with viruses, there are no risks as the others mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Such a technique would be expected to play an important role in advanced medical technologies like gene therapy and regenerative medicine through establishment of iPS (induced pluripotent stem) cells. A technique that uses discharge plasma irradiation was invented by Satoh, who is one of the authors, and his group in 2002 [4] and was reported by Ogawa in 2005 [5]. Since this technique is free from adverse effect associated with viruses, there are no risks as the others mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of its translation into major healthcare innovations include tissue ablation and coagulation, disinfection of food and living tissues, wound healing, and even cancer treatment23242526. Several groups have reported that plasma jet with pulsed high frequency could increase the cell permeability and delivery of GFP vectors in mammalian cells such as HeLa cells, CHL cells, Jurkat cells, Hacat cells and MCF-7 cells272829. Leduc et al .…”
mentioning
confidence: 99%
“…One investigation described the use of plasma to deliver DNA into primary neuronal cells in vitro. 24 Another study by Connolly et al demonstrated increased transfection of a luciferase-expressing plasmid in the skin when the injection area was concomitantly exposed to helium plasma. 21 It has been recently demonstrated in several studies that helium plasma exposure enhances the vaccination efficacy of a plasmid-expressing HIV-1 gp120 (envelope glycoprotein) in mice when compared with injection only.…”
Section: Resultsmentioning
confidence: 99%